Vapor phase catalytic photooxidation of sulfides to sulfoxides: application to the neutralization of sulfur mustard simulants. Issue 6 (2nd March 2022) - Oheix, Emmanuel; Gravel, Edmond; Doris, Eric
Abstract : A porphyrin-based setup was developed for the selective photooxidation of sulfides to the corresponding sulfoxides. The process operates in the vapor phase under air atmosphere. Abstract : A visible-light photocatalytic approach was developed for the aerobic oxidation of sulfides into the corresponding sulfoxides, including sulfur mustard simulants. The heterogeneous catalytic system is selective, operates in the gas phase with very low catalytic loadings, uses oxygen from the air as oxidant, and can be readily recycled and reused.